The Composition of El morador (1944) by Javier Sologuren: Thematic Structure and Stylistic Unity - Guizado-Yampi, Renato (2021)
El morador is the first poetry collection of Javier Sologuren, published in 1944 as a brochure of the journal Historia (n°8). Many critics argue that in these poems the author demonstrates his deft skills with language and poetic forms. That rigorous work of Sologuren also operates composing the set as a structure which integrates the poems in a sequence and meaning aligned with the conception of poetry they express; however, the critics do not mention that aspect of the collection. This paper examines that point on the writing of El morador (which was conceived with a sequential structure and with stylistic unity) and interprets it on the basis of the analysis of each poem.